2016
DOI: 10.1177/2165079916653414
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Engagement

Abstract: This study's purpose was twofold: first, to examine the relative importance of job demands and resources as predictors of burnout and engagement, and second, the relative importance of engagement and burnout related to health, depressive symptoms, work ability, organizational commitment, and turnover intentions in two samples of health care workers. Nurse leaders ( n = 162) and licensed emergency medical technicians (EMTs; n = 102) completed surveys. In both samples, job demands predicted burnout more strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 37 publications
6
34
1
Order By: Relevance
“…Two early studies that used the Burnout Scale for Health Professionals found burnout among EMS providers was more prevalent than in other healthcare professionals in the U.S. 3 , 4 Two recent surveys conducted in U.S. paramedics and EMTs captured burnout measures using the Oldenburg Burnout Inventory and the Copenhagen Burnout Inventory. 11 , 12 One reported a work-related burnout prevalence of 30% in paramedics and 19% in EMTs, 11 and both found burnout was associated positively with turnover intentions and absenteeism. 11 , 12 In the only prior report of MBI data from a cohort of U.S. paramedics, mean scores for EE, DP, and PA were 19.2, 9.3, and 28.1, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two early studies that used the Burnout Scale for Health Professionals found burnout among EMS providers was more prevalent than in other healthcare professionals in the U.S. 3 , 4 Two recent surveys conducted in U.S. paramedics and EMTs captured burnout measures using the Oldenburg Burnout Inventory and the Copenhagen Burnout Inventory. 11 , 12 One reported a work-related burnout prevalence of 30% in paramedics and 19% in EMTs, 11 and both found burnout was associated positively with turnover intentions and absenteeism. 11 , 12 In the only prior report of MBI data from a cohort of U.S. paramedics, mean scores for EE, DP, and PA were 19.2, 9.3, and 28.1, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 One reported a work-related burnout prevalence of 30% in paramedics and 19% in EMTs, 11 and both found burnout was associated positively with turnover intentions and absenteeism. 11 , 12 In the only prior report of MBI data from a cohort of U.S. paramedics, mean scores for EE, DP, and PA were 19.2, 9.3, and 28.1, respectively. 13 MBI data from ambulance personnel outside the U.S. have been reported, 6 , 15 18 , 32 but variability in defining burnout as a dichotomous construct makes inter-study comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moral distress has been studied extensively in high-intensity nursing care specialties such as critical care (Bruce et al, 2015;Mason et al, 2014;Rushton et al, 2015), in general medical-surgical nursing (Rathert et al, 2016;Whitehead et al, 2015), and in nurse leaders (Pavlish et al, 2016). Resilience (Brown et al, 2018) and workplace engagement (Carter & Tourangeau, 2012;Fragoso et al, 2016;Laschinger, 2012) have also been studied in the general population of nurses. However, resilience, moral distress, and workplace engagement have not been examined together in the ED nursing population (Adriaenssens et al, 2015;Hsieh et al, 2016;Wolf et al, 2016).…”
Section: Protecting Workplace Engagement From Moral Distress Effectsmentioning
confidence: 99%